The effect of adding probiotics or prebiotic to the diet on the characteristics of local Iraqi goat carcasses and fat deposition - Maithem K. A. Al-Galiby (University of Thi-Qar Journal of agricultural research, 2024)
The present study aimed to find out the effect of adding both the probiotics (3 g / kg feed) or the prebiotic (2 g / kg feed) to the local Iraqi kids diets on some characteristics of carcasses quantitative and qualitative traits. The study used 16 male kids who were evenly distributed over four treatments. The first treatment was fed 60% concentrated diet (included 20% wheat flour, 25% wheat bran, 20% corn, 7% soybeans, 3% salts and vitamins) with 40% alfalfa hay (control), while the remaining three groups were fed the same control diet in addition to 3 g probiotic/kg feed, 2 g prebiotic/kg feed or 1.5 probiotic + 1 gm prebiotic/ kg feed, respectively. The average weight of the kids was 18.90 kg at the start of the study and their average age was 4-5 months. The duration of the study was 105 days, including 15 days for adaptation. Diets were provided based on 3% of body weight. Kids were slaughtered and the carcasses cooled to 2 ° C for 24 hours. A range of measurements were made that included carcass characteristics, physical composition, muscle and bone distribution, and fat distribution pattern in the carcass. The results showed that the groups that were added to the probiotic diets significantly outperformed the control group in all measurements of carcass cuts. Both probiotic and prebiotic groups exceeded the control group in cold carcass weight, dressing percentage, fat layer thickness and eye muscle area. The three treatments also recorded the highest dressing compared to the control treatment.